Effect of age and sex on efficacy and tolerability of β blockers in patients with heart failure with reduced ejection fraction: individual patient data meta-analysis. (20th April 2016) - Kotecha, Dipak; Manzano, Luis; Krum, Henry; Rosano, Giuseppe; Holmes, Jane; Altman, Douglas G; Collins, Peter D; Packer, Milton; Wikstrand, John; Coats, Andrew J S; Cleland, John G F; Kirchhof, Paulus; et al.
Abstract : Objectives To determine the efficacy and tolerability of β blockers in a broad age range of women and men with heart failure with reduced ejection fraction (HFrEF) by pooling individual patient data from placebo controlled randomised trials. Design Prospectively designed meta-analysis of individual patient data from patients aged 40-85 in sinus rhythm at baseline, with left ventricular ejection fraction <0.45. Participants 13 833 patients from 11 trials; median age 64; 24% women. Main outcome measures The primary outcome was all cause mortality; the major secondary outcome was admission to hospital for heart failure. Analysis was by intention to treat with an adjusted one stage Cox proportional hazards model. Results Compared with placebo, β blockers were effective in reducing mortality across all ages: hazard ratios were 0.66 (95% confidence interval 0.53 to 0.83) for the first quarter of age distribution (median age 50); 0.71 (0.58 to 0.87) for the second quarter (median age 60); 0.65 (0.53 to 0.78) for the third quarter (median age 68); and 0.77 (0.64 to 0.92) for the fourth quarter (median age 75). There was no significant interaction when age was modelled continuously (P=0.1), and the absolute reduction in mortality was 4.3% over a median follow-up of 1.3 years (number needed to treat 23). Admission to hospital for heart failure was significantly reduced by β blockers, although this effect was attenuated at older ages (interaction P=0.05). There was no evidence of an interaction between treatment effect and sex in any age group. Drug discontinuation was similar regardless of treatment allocation, age, or sex (14.4% in those give β blockers, 15.6% in those receiving placebo). Conclusion Irrespective of age or sex, patients with HFrEF in sinus rhythm should receive β blockers to reduce the risk of death and admission to hospital. Registration PROSPERO CRD42014010012; Clinicaltrials.gov NCT00832442 .